Mental health policy developments in Latin America - R.D. Alarcón; S.A. Aguilar-Gaxiola (The World Health Organization, 2000)
New assessment guidelines for measuring the overall impact of mental health problems in Latin America have served as a catalyst for countries to review their mental health policies. Latin American countries have taken various steps to address long-standing problems such as structural difficulties, scarce financial and human resources, and social, political, and cultural obstacles in the implementation of mental health policies and legislation. These policy developments, however, have had uneven results. Policies must reflect the desire, determination, and commitment of policy-makers to take mental health seriously and look after people's mental health needs. This paper describes the development of mental health policies in Latin American countries, focusing on published data in peer-reviewed journals, and legislative change and its implementation. It presents a brief history of mental health policy developments, and analyzes the basis and practicalities of current practice.